ANALISIS PENGARUH DESAIN MASKOT DALAM IDENTITAS VISUAL PADA OLYMPUS 2.0 EXHIBITION - Adytia Putra Hermanto, Adytia Putra Hermanto; Hendri Kremer; Fajar Persada Supandi (JURNAL RUPA MATRA, 2024)
Mascots in branding design and art exhibition events have a significant visual influence on the image of the event. In this research, the mascot that will be analyzed for its visual influence and identity is the mascot of the Olympus 2.0 art and design exhibition event of Batam Institute of Technology. The research method used is a qualitative research method with a semantic analysis approach that examines the visual aspects of the Olympus 2.0 mascot. The mascot becomes an iconic representation of the event, and this visual element plays a key role in attracting attention, building identity, and communicating the event's message to the audience. the use of mascots as a visual element in branding design and art exhibition events is a powerful strategy to create a strong image and connect audiences with the event. Olympus 2.0 mascot takes the representative of Tarsier animal named Pras by taking the tagline "invisible but impactful". this research aims to provide valuable insights into the important role played by the visual influence of mascots in the branding of art and design events, as well as its impact on the success and acceptance of such events.